The life and problems connected with Władysław Warneńczyk (of Varna) in the literary creation of Leopold Kielanowski - Hojdis, Bogdan (Balcanica Posnaniensia. Acta et studia, 1997)
The article is devoted to an analysis of Leopold Kielanowski’s book The Odyssey of Władysław of Varna, published posthumously in 1991 on the basis of Radio Free Europe broadcasts. The author examines the literary construction of Władysław of Varna’s fate after the Battle of Varna and the problem of the boundary between historiography and historical literature. The aim of the study is to assess the character of Kielanowski’s work and to present the mechanisms of constructing an alternative biography of the king. The author employs literary and historical analysis of the book, referring to historical sources, Portuguese legends, and traditions associated with the figure of Henry the German. The article demonstrates that Kielanowski, finding no reliable evidence of Władysław III’s death at Varna, created a hypothetical story of the king’s later fate, according to which he survived the battle, traveled through the Middle East, and then settled on Madeira under an assumed name. The author emphasizes that Kielanowski’s work does not meet the criteria of a scholarly study, but constitutes an example of historical literature strongly marked by emotional and ideological elements. The results of the analysis indicate that The Odyssey of Władysław of Varna functions as a literary reinterpretation of the Władysław of Varna myth, combining elements of history, legend, and Romantic imagination.